The role of media in the Arab Revolutions: the case of Syria - Bakour Mohamad, Bachar (Universiti Teknologi MARA, 2020)
Whether in the time of war or peace, media, considered the ‘Fourth Authority’, must struggle to present the truth to the public, making no concession to any kind of authority, whether legislative, executive or judicial. This study, which adopts descriptive-analytical method, gives a brief account of the 2011 Arab popular revolts with reference to the media's significant role in war/conflict. Then, it investigates the manipulative role played by the official and semi-official visual media during the first six months of the Syrian Revolution. As a tool in the hand of the regime, these media outlets worked on propagating the regime’s adopted narrative. This narrative depicts the non-violent protestors as terrorist gangs, and conspirators supported by foreign imperial powers. The media’s manipulative role in the presentation of events and dissemination of information falls under the following categories: misrepresenting reports; the blame game; defaming the opponent; manipulating religious discourse and polishing the image of the regime. Examples are furnished for each category. Finally, the study calls for the core values of ethical media from the Islamic perspective, providing a blueprint for those who aspire to engage in the public information sphere and to ensure reliability and credibility in their profession.